2019
DOI: 10.1111/acps.13104
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use in early adulthood is prospectively associated with prescriptions of antipsychotics, mood stabilizers, and antidepressants

Abstract: Cannabis use in early adulthood is prospectively associated with prescriptions of antipsychotics, mood stabilizers, and antidepressants Rognli EB, Bramness JG, von Soest T. Cannabis use in early adulthood is prospectively associated with prescriptions of antipsychotics, mood stabilizers, and antidepressants.Objective: Cannabis is an acknowledged risk factor for some mental disorders, but for others the evidence is inconclusive. Prescribed medicinal drugs can be used as proxies for mental disorders. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…We find it unlikely that erroneous categorization could explain a large share of the difference in risk found in the present study. Also, receiving a prescription of a psychotropic drug has been used as an indirect measure of mental disorders in several previous studies (McKenzie, Murray, & Booth, 2013 ; Mok et al, 2013 ; Rognli, Bramness, & von Soest, 2020 ; Wium-Andersen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We find it unlikely that erroneous categorization could explain a large share of the difference in risk found in the present study. Also, receiving a prescription of a psychotropic drug has been used as an indirect measure of mental disorders in several previous studies (McKenzie, Murray, & Booth, 2013 ; Mok et al, 2013 ; Rognli, Bramness, & von Soest, 2020 ; Wium-Andersen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have explored the relationship between cannabis and depression and a review article from 2014 concluded that cannabis use is associated with a greater risk of developing depression [ 15 ]. This is supported by a Norwegian study from 2020 showing that cannabis use was related to later use of antipsychotics, mood stabilizers and antidepressants [ 16 ]. A study by Kvitland et al has shown that the use of cannabis is associated with earlier disease onset and poorer functioning in patients with bipolar disorder [ 17 ].…”
Section: Introductionmentioning
confidence: 64%
“…We identified 75 studies for inclusion, 13, of which 59 were included in the primary meta-analyses. 13,47,49,50,52,53,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][71][72][73][75][76][77][78][80][81][82]84,85,[87][88][89]91,92,[94][95][96]100,[102][103][104][105][106][107][108][109][110][111]…”
Section: Literature Searchmentioning
confidence: 99%